Badania archeologiczne w Bydgoszczy w świetle literatury i dokumentacji konserwatorskiej (Kronika Bydgoska, 2012)
Archaeology is a still developing discipline of science, and excavation examinations are an invaluable source of information about the past. With the passage of time, it became necessary to tracę the history of this scientific discipline. Studies on individual centres conducting archaeological research, being a review and summary of their achievements, started to appear recently. The article is based on a register of archaeological research conducted in the area of Bydgoszcz. The text was prepared on the basis of materials gathered in the Bydgoszcz representation of the Voivodeship Office for the Preservation of Historical Sites in Toruń, thus it is also a picture of the functioning of this Office in the scope of conducting and supervising archaeological works in Bydgoszcz. The character of the text demanded passing over other aspects of the operations of this institution and people connected with it. However, I do hope that it will become the beginning of morę comprehensive research on the history and operations of the Bydgoszcz archaeological centre, and the place of researchers connected with Bydgoszcz in its structures and scientific undertakings.